Precaution or Integrated Responsibility Approach to Nanovaccines in Fish Farming? A Critical Appraisal of the UNESCO Precautionary Principle - Myhr, Anne Ingeborg (Springer Netherlands, 2011)
Nanoparticles have multifaceted advantages in drug administration as vaccine delivery and hence hold promises for improving protection of farmed fish against diseases caused by pathogens. However, there are concerns that the benefits associated with distribution of nanoparticles may also be accompanied with risks to the environment and health. The complexity of the natural and social systems involved implies that the information acquired in quantified risk assessments may be inadequate for evidence-based decisions. One controversial strategy for dealing with this kind of uncertainty is the precautionary principle. A few years ago, an UNESCO expert group suggested a new approach for implementation of the principle. Here we compare the UNESCO principle with earlier versions and explore the advantages and disadvantages by employing the UNESCO version to the use of PLGA nanoparticles for delivery of vaccines in aquaculture. Finally, we discuss whether a combined scientific and ethical analysis that involves the concept of responsibility will enable approaches that can provide a supplement to the precautionary principle as basis for decision-making in areas of scientific uncertainty, such as the application of nanoparticles in the vaccination of farmed fish.